Man in a World of Values. What is Applied Cultural Studies? - Rotengruber, Przemysław (Journal of Applied Cultural Studies, 2015)
The aim of the study is to present the project of applied cultural studies – a result of work inspired by the output of representatives of the Poznań School of Methodology. Florian Znaniecki, Jerzy Topolski and Jerzy Kmita give a picture of culture the research of which is – to put it as briefly as possible – subjected to the principle of diversity in the models constituting it. Human motifs demand careful research precisely because they escape a simple comparison of arguments resulting from the knowledge of social facts. In accordance with this assumption the concept of applied cultural studies is accompanied by the conviction that heterogeneous systems of models of culture may become the object of development.